Representasi Politik Perempuan Pekerja Migran Indonesia (PPMI) di Parlemen: Peluang dan Tantangan - Azmy, Ana Sabhana Azmy (Yayasan Jurnal Perempuan, 2024)
The absence of Indonesian women migrant workers (Perempuan Pekerja Migran Indonesia/PPMI) in parliament reflects the unfulfilled political rights of citizens. With various problems of election violations such as double DPT, overseas election systems that are vulnerable to manipulation through postal and drop box methods indicate the vulnerability of the distribution of voting rights as a political right of a migrant worker, where the majority of migrant workers are women who work in the informal sector. The presence of migrant workers in parliament is important to accommodate political rights, both voting rights and the distribution of opinions. Their political representation in parliament will reflect the implementation of democratic values, and be a positive example for other women in politics, especially in the context of gender justice. This paper uses the gender justice framework of Squires, the political theory of presence from Anne Phillips, and the representation theory from Hanna Pitkin to discuss the urgency of representation of woman migrant workers in parliament as a reflection of the fulfillment of political rights. The research method used is a critical and in-depth analysis of relevant literature studies.